Exploring the nutritional values, volatile compounds, health benefits, and potential food products of chilli (Capsicum annuum): A comprehensive review - Mohd Ali, Maimunah; Khalid, Nurul Izzah; Wondi, Mohd Hafizz; Haris, Nur Izzah Nabilah; Megat Ahmad Azman, Puteri Nurain (Elsevier, 2025)
Chilli holds significance as a vital agricultural vegetable crop for its economic contributions and medicinal properties inherent in its fruit. Chilli (Capsicum annuum) is widely consumed globally for its fiery flavour but also its diverse nutritional properties. The demand for chilli has vastly increased especially in the development of promising chilli-based food products worldwide. This comprehensive review discusses the multifaceted aspects of chilli, encompassing the nutritional composition, volatile compounds, health benefits, and various potential uses of food products. Chilli is rich in essential vitamins, minerals, nutrients, and phytochemicals contents. The health-promoting effects of chilli, including antioxidant, anti-inflammatory, anticancer, antiobesity, and antifungal activities, are primarily attributed to its bioactive constituents such as capsaicin, capsanthin, quercetin, polyphenols, flavonoids, and vitamins A, C, and E, which modulate oxidative stress, inflammatory pathways, and cellular apoptosis. The abundant volatile profile elucidates the complex aroma compounds responsible for the distinctive scent and flavour of chillies. Beyond its culinary appeal, chilli demonstrates remarkable potential in various food products, ranging from condiments and sauces to functional foods and cuisines. This review uniquely integrates multiple perspectives across disciplines, which provide a holistic synthesis that bridges nutritional science, food technology, and health, while also discussing recent innovations and future directions for chilli-based applications. The challenges and future perspectives related to chillies are also highlighted. This integrative approach offers a broader understanding role of chillies as both culinary staple and multifunctional ingredient with promising health and commercial implications.